Religious Voluntarism in The Youth Muslim Philanthropy Movement In Medan - Sahran Saputra; Nirwansyah Putra (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2021)
This research discusses religious voluntarism in the philanthropic movement carried out by the Muslim youth hijrah community. The purpose of this study is to find out how the patterns of voluntarism in the philanthropic movement of Muslim youth in Medan. This research uses qualitative methods with data collection techniques through observation, interviews, and literature study. The results of the study reveal the idea of the movement that has been carried out by the younger generation of Muslims refers to religious attitudes. This condition is a response to the social conditions and religiosity of Muslim youths in the city of Medan. This community conducts a voluntary recruitment pattern. This is a motivation for young Muslims in the city of Medan to improve themselves towards piety, both individually and socially by referring to religious teachings in the Qur'an and hadith. Building Islamic values as a transitional spirit in the commitment and shared values of the organization and all its managers. These organizational values and commitments lead to the spirit of religious voluntarism.Keywords: Religious voluntarism, Hijrah movement, Muslim youth